Psychological Analysis of Specialists of the Institute for Leadership Development (National Technology Initiative): Training of Entrepreneurs of Technological Startups - A. V. Vlasov; A. Ilyin; M. К. Nurbekov (Управленческие науки, 2019)
The paper presents the results of a comprehensive psychological study of the professional network community of the Institute for the development of leaders as a strategic initiative, “Agency for strategic initiatives to promote new projects” (ASI). Based on its results, the authors attempt to formalize and justify the psychological determinants of personality, the purposeful impact and education of the younger generation, nudge and the correction of “mature” entrepreneurs will directly affect their personal growth, correspond to their individual development path, activate the activity “under the flag” of the National technology initiative (NTI) and the strategy of national technological development (NTD). The article presents the results of the study of individual psychological indicators of the professional community representatives of the Institute for Leadership Development ASI. Only representatives of the russian technological elite can be the main drivers of socio-economic growth of the national economy in the next 5–10–20 years. The Government of the Russian Federation has relied on the development of science and technology in its development Strategy.